Foraminifera as sea-level change indicators, Guaratiba Mangrove, Rio de Janeiro - Brazil - Laut, Lázaro L. M.; Koutsoukos, Eduardo A. M.; Rodrigues, Maria Antonieta C. (Anuário do Instituto de Geociências, 2006)
Abstract